Contribution of classroom practice to the training of new teachers: a Bachelor's experience report (Research, Society and Development, 2021)
The present study aims to report the experience and activities developed by a Bachelor in the execution of his Teaching Internship, as a postgraduate student at Master's level. The internship was carried out in the course of Bachelor in Biomedicine, of the Federal University of Delta of Parnaíba. The trainee was responsible for selecting, preparing and performing theoretical and practical classes. The activities were conducted in the disciplines of Bacteriology, Virology and Practices in Biomedicine II. Under the supervision of the responsible teacher for those curricular components, the trainee fulfilled a total workload of 30 hours, executing the proposed activities. That experience represented a moment of approximation to the classroom environment, making possible to understand the challenges of teaching in higher education. The execution of both theoretical and practical classes in laboratories contributed to understanding the process of development of new biomedical scientists. Since professional Bachelor's did not include preparation for a teaching career, this activity represented an important strategy for the academic formation of a new Master in the health field.